Squawking about persistently higher inflation? - LAM, Thomas (Institutional Knowledge at Singapore Management University, 2021)
All signs point to an uncertain path for inflation in the future. While inflation is set to stay prospectively higher in the US in the near-term, it's unlikely to remain so.